Enhancement of energy storage capacity in lithium polymer batteries incorporated with zirconium oxide nano powders. (2021) - Murugandhan, D.; Valli, R.; Senthilkumar, N.; Arunmozhi, S.
Abstract: In this work, three poly-methyl methacrylate (PMMA) hosted solid polymer electrolyte systems were prepared by a solution cast technique. A fixed amount of PMMA and nano Zirconium dioxide (ZrO2 ) were implemented as ceramic filler and lithium hexafluorophosphate (LiPF6 ) as dopant salt. The study was carried out using Electrochemical Impedance Spectroscopy (EIS) and Scanning Electron Microscope (SEM). The integrating 20 wt% of Propylene carbonate (PC) into PMMA enhanced the ionic conductivity with another addition of 5 wt% of LiPF6, the ionic conductivity is increased to from 1.94 × 10–11 Scm −1 to 2.97 × 10–09 Scm −1 . This has inferred the enhancement of charge carrier density in the polymer electrolyte. A further addition of ceramic fillers with 10 wt% of ZrO2, boosted the ionic conductivity to 9.45 × 10–11 Scm −1 and 4.44 × 10–9 Scm −1, respectively. The SEM images showed the formation of three-dimensional networks with dispersion of ceramic fillers. It can be concluded that appropriate amount of lithium salt (5 wt% of LiPF6 ) and ceramic filler (10 wt% of ZrO2 ) enhances the ionic conductivity of the PMMA-based solid polymer electrolyte. The electrical conductivity of PMMA-LiPF6 polymer blend with different concentrations of ZrO2 as a nano filler has been studied. The polymer blend electrolyte was prepared in the form of thin films using solution casting technique. The blend was characterized by Scanning Electron Microscopy (SEM).